A MULTIPURPOSE AND NOVEL CARRIER FOR DRUG DELIVERY AND TARGETING - VIROSOMES - Kapoor, D; Vyas, R B; Lad, C; Patel, M (Journal of Drug Delivery and Therapeutics, 2013)
There is presently passionate investigation bustle aimed at the improvement of new delivery systems for vaccines. The aspiration is to identify best possible methods for presenting target antigens to the immune system in a manner that will elicit immune responses appropriate for protection against, or treatment of, a specific disease. Virosomes are biocompatible, biodegradable, nontoxic, and non-autoimmunogenic, attempts have been made to use them as vaccines or adjuvant as well as delivery systems for drugs, nucleic acids, or genes for therapeutic purposes. Influenza virus is the most common virus of choice. There are at present numerous factors that are creating pressure to develop delivery systems for vaccines. First, in the existing regulatory milieu, there is a budding prerequisite to build up vaccines that are very well defined in molecular requisites. Unambiguous targeting and liberation as well as the display of antigens on the surface of Professional antigen-presenting cells (APCs) are key issues in the blueprint and improvement of new-generation vaccines intended at the initiation of both humoral and cell mediated immunity. Prophylactic vaccination in opposition to infectious diseases in general aims at the generation of humoral immune responses to prevent infection. However, mmunization with live vaccines bears the peril of causing ailment. For that reason, unconventional vaccine delivery systems are must to produce better immune response. Virosomal technology presents a fresh urbane delivery system to congregate these challenges. On the whole, virosomes guard pharmaceutically active substances from proteolytic dilapidation and low pH within endosomes, allowing their contents to linger intact when they get in touch with the cytoplasm. This is a foremost benefit of virosomal transporter systems over other drug-delivery vehicles, including liposomal and proteoliposomal carrier systems.Â